The goals of competition law for merger analysis in developing jurisdictions : a critical appraisal of merger analysis under Kenyan competition law - Van Heerden, C.M. (Corlia) (University of Pretoria, 2023)
Thesis (LLD (Mercantile Law))--University of Pretoria, 2023.